A 'Nobel' Look at Metabolism. (December 2018) - Xiong, Jianhua
Abstract : Metabolism has recently been in the spotlight because of technical advances in metabolite measurement; however, it is not a new topic in the Nobel Prize's history. Emerging evidence suggests that metabolism is more complex than was previously believed. Retrospective analysis of the Nobel Prize-winning metabolic discoveries may inspire future studies.